2011
DOI: 10.3897/zookeys.104.763
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Phyllognathopodidae (Copepoda, Harpacticoida): re-examination of Phyllognathopus viguieri (Maupas, 1892) and Parbatocamptus jochenmartensi Dumont and Maas, 1988, proposal of a new genus for Phyllognathopus bassoti Rouch, 1972, and description of a new species of Phyllognathopus

Abstract: The family Phyllognathopodidae (Crustacea, Copepoda, Harpacticoida) is heavily affected by the floating taxonomic status of the type-genus Phyllognathopus. A revision of the different character states displayed by members of the family is presented, and new phylogenetically informative characters are described, enlarging the analysis to the remaining genera of the family, Parbatocamptus and Allophyllognathopus. Phyllognathopus viguieri (Maupas, 1892) and Parbatocamptus jochenmartensi Dumont and Maas, 1988 are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The Central-Apennines hotspot was mainly driven by the Canthocamptidae (5 genera, 14 species) with a good representativeness of the Ameiridae (2 genera, 11 species), followed by the Parastenocarididae (5 genera, 8 species), the Ectinosomatidae (1 genus, 3 species) and the Phyllognathopodidae, with the sole stygobitic species of the genus Phyllognathopus known worldwide so far, P. inexspectatus (Galassi et al 2011). This hotspot hosted a relatively low species richness if compared to the other ones, along with high endemicity score (10 spot endemics), the highest taxonomic distinctness at the family level, high phylogenetic rarity (e.g.…”
Section: Distribution Of Groundwater Harpacticoids In the Hotspots Anmentioning
confidence: 99%
“…The Central-Apennines hotspot was mainly driven by the Canthocamptidae (5 genera, 14 species) with a good representativeness of the Ameiridae (2 genera, 11 species), followed by the Parastenocarididae (5 genera, 8 species), the Ectinosomatidae (1 genus, 3 species) and the Phyllognathopodidae, with the sole stygobitic species of the genus Phyllognathopus known worldwide so far, P. inexspectatus (Galassi et al 2011). This hotspot hosted a relatively low species richness if compared to the other ones, along with high endemicity score (10 spot endemics), the highest taxonomic distinctness at the family level, high phylogenetic rarity (e.g.…”
Section: Distribution Of Groundwater Harpacticoids In the Hotspots Anmentioning
confidence: 99%
“…Some copepod species in the study, D. languidoides, E. serrulatus, M. viridis, T. prasinus, P. chiltoni, T. prasinus, A. crassa, N. stammeri, and P. viguieri are reported by various researchers to live in a wide range of habitats such as caves, wells, groundwater systems, spring waters, ponds, rivers, backwaters, benthic zone of lakes, marshes and swamps (Morton & Bayly, 1977;Pesce & Maggi, 1981;Berzins & Bertilsson, 1990;Lehman & Reid, 1992;Karaytuğ, 1999;Dussart & Defaye, 2006;Lee & Chang, 2007;Tang & Knott, 2008;Galassi et al, 2011;Iepure et al, 2014;Bruno & Cottarelli, 2015;Iepure et al, 2016;Bozkurt, 2017). T. dybowskii, one of the copepod species recorded in the study, which was not reported from groundwater and wells, is in perennial ponds, coastal waters (occasional), pelagic zone of ponds and lakes, lives in small water bodies (Maier, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Calanoids are predominantly planktonic, and cyclopoids can either be planktonic (also in subterranean lakes and pools) or reside in interstitial habitats, however preferring mediumcoarse sediments. Harpacticoids are almost exclusively benthic organisms, either inhabiting the minute voids among the sediment particles or living as epiphytic in the benthos (e.g., in mosses or macrophytes, swimming or gliding on the leaf surfaces in proximity of the benthic surface) or as hyperbenthic, swimming in the few millimeters above the sediment surface or alternatively in phytotelmata (Reid 2001;Galassi et al 2011). In groundwater, they are exclusively linked to benthic habitats (Galassi et al 2009a).…”
Section: Sensitivity Of Freshwater Copepodsmentioning
confidence: 99%